Regional cortical thinning in multiple sclerosis and its relation with cognitive impairment: A multicenter study. (June 2016) - Tillema, JM; Hulst, HE; Rocca, MA; Vrenken, H; Steenwijk, MD; Damjanovic, D; Enzinger, C; Ropele, S; Tedeschi, G; Gallo, A; Ciccarelli, O; Rovira, A; et al.
Objectives: The objectives of this paper are to compare in a multicenter setting patterns of regional cortical thickness in patients with relapsing–remitting multiple sclerosis (RRMS) and cognitive impairment (CI) and those cognitively preserved (CP), and explore the relationship between cortical thinning and cognitive performance. Methods: T1-weighted isotropic brain scans were collected at 3T from seven European centers in 60 RRMS patients and 65 healthy controls (HCs). Patients underwent clinical and neuropsychological examinations. Cortical thickness (CTh) measures were calculated using FreeSurfer (failing in four) and both lobar and vertex-based general linear model (GLM) analyses were compared between study groups. Results: Twenty (36%) MS patients were classified as CI. Mean global CTh was smaller in RRMS patients compared to HCs (left 2.43 vs. 2.53 mm, right 2.44 vs. 2.54 mm, p < 0.001). Multivariate GLM regional analysis showed significantly more temporal thinning in CI compared to CP patients. Verbal memory scores correlated to regional cortical thinning in the insula whereas visual memory scores correlated to parietal thinning. Conclusions: This multicenter study showed mild global cortical thinning in RRMS. The extent of thinning is less pronounced than previously reported. Only subtle regional differences between CI and CP patients were observed, some of which related to specific cognitive domains.